Original paperExpression of skin lesions in surgically treated patients with neurofibromatosis type 1 - Rykała, Jan; Iljin, Aleksandra; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Neurofibromatosis type 1 is a phacomatosis causing pathological alterations in the skin and nervous system. Aetiopathology depends on genetic factors but in some of the patients we do not observe a positive family history of disease. Therapy is symptomatic – surgical excision. Lesions of the central nervous system need neurosurgical treatment. Material and methods: In the Plastic, Reconstructive and Aesthetic Surgery Clinic of the Medical University of Łódź between 1996 and 2008 we examined 15 patients. Surgical procedures were performed in 10 patients (7 female and 3 male). The age of patients was 13-62 years. Results: In this paper we present a clinical and diagnostic analysis of patients with Recklinghausen disease type 1. The analyses of the examined patients show the change in numbers of pathological lesions in differences parts of the body. Surgical treatment was without complications but with good functional and aesthetic results. Conclusions: Skin lesions in neurofibromatosis type 1 should be removed as early as possible when the tumours is small. It is important for functional and aesthetic reasons.